A systematic evolution of ligands by exponential enrichment workflow with consolidated counterselection to efficiently isolate high‐affinity aptamers. Issue 1 (12th January 2020) - Rosch, Jonah C.; Balikov, Daniel A.; Gong, Franklin; Lippmann, Ethan S.
Abstract : Efficient selection of nucleic acid aptamers with high affinity and specificity for a broad range of targets remains challenging. Historically, aptamer selections have been protracted and tedious processes, often requiring double‐digit rounds of selection to converge nucleic acid pools into a small number of prospective high‐affinity aptamers. More recently, the use of microfluidic devices and specialized equipment has helped streamline the aptamer selection process, but these platforms are not necessarily accessible to the broad research community. Here, we demonstrate that aptamers with high affinity and moderate specificity can be obtained with a conventional selection workflow that is modified to include facile methods for increasing partitioning and enhancing selection stringency. This process exposes an immobilized protein target to a single‐stranded DNA library, followed by washing with buffer that contains the undesired off‐target(s), with both steps occurring under constant perfusion using a standard peristaltic pump. Prospective aptamers are then eluted, amplified by an emulsion polymerase chain reaction, regenerated to single strands by enzymatic digestion, and resubjected to the selection procedure. We validated this selection scheme using the platelet‐derived growth factor (PDGF) family, whereby we successfully isolated nanomolar affinity aptamers against PDGF‐BB with specificity comparable to an aptamer selected using a microfluidics‐based approach. Abstract : This manuscript describes a shortened approach for generating nucleic acid aptamers against immobilized protein targets. The resultant aptamers have high affinity and moderate specificity for structurally‐similar proteins.